PELAKSANAAN KPSP SEBAGAI UPAYA DETEKSI DINI PERKEMBANGAN ANAK DI POSYANDU DESA MEKAR SARI - Hutabarat, Vitrilina; Sari, Husna; Nainggolan, Nurcahaya (INSTITUT KESEHATAN DELI HUSADA, 2025)
Developmental disorders in children can significantly hinder their potential to achieve an optimal quality of life. Prevention of these disorders relies heavily on systematic early detection efforts. At the Mekar Sari Village Integrated Health Post (Posyandu), problems related to growth disorders and developmental delays, exacerbated by a lack of early detection practices, pose a public health challenge. This community service activity, implementing the KPSP (Pre-Screening Development Questionnaire), aims to detect developmental disorders in children early using the Pre-Screening Development Questionnaire (KPSP). Screening was conducted on children aged 6 - 60 months using a descriptive observational approach. The KPSP implementation involved parents completing the questionnaire, followed by direct observations to assess the children's motor, language, and social aspects. The results revealed that 82% of the children exhibited age-appropriate development, 16% fell into the questionable category, and 2% experienced developmental deviations. Nutritional status was also monitored, showing that 80% of the children were categorized as having good nutrition, 18% were overweight, and 2% were undernourished. This activity had a positive impact by raising parental awareness about the importance of optimal stimulation and regular monitoring of child growth and development. With support from local governments and technological innovations, this program hasthe potential to be implemented in other regions to prevent future health and developmental problems in children.